2008
DOI: 10.1038/jcbfm.2008.44
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin-1 Reduces Histopathology and Improves Functional Outcome after Controlled Cortical Impact in Mice

Abstract: Necroptosis is a newly identified type of programmed necrosis initiated by the activation of tumor necrosis factor alpha (TNFalpha)/Fas. Necrostatin-1 is a specific inhibitor of necroptosis that reduces ischemic tissue damage in experimental stroke models. We previously reported decreased tissue damage and improved functional outcome after controlled cortical impact (CCI) in mice deficient in TNFalpha and Fas. Hence, we hypothesized that necrostatin-1 would reduce histopathology and improve functional outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
211
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(229 citation statements)
references
References 32 publications
17
211
1
Order By: Relevance
“…This is the first study to show the neuroprotective efficacy of necrostatin in any model of neonatal brain injury. Previous studies have shown that necrostatin is neuroprotective in adult mouse stroke and traumatic brain injury models as shown by histologic and behavioral outcomes (Degterev et al, 2005;You et al, 2008). Protection in necrostatin-treated neonatal mice is demonstrable in the ipsilateral forebrain and thalamus at 4 days (P11) and persists at 21 days (P28) after HI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is the first study to show the neuroprotective efficacy of necrostatin in any model of neonatal brain injury. Previous studies have shown that necrostatin is neuroprotective in adult mouse stroke and traumatic brain injury models as shown by histologic and behavioral outcomes (Degterev et al, 2005;You et al, 2008). Protection in necrostatin-treated neonatal mice is demonstrable in the ipsilateral forebrain and thalamus at 4 days (P11) and persists at 21 days (P28) after HI.…”
Section: Discussionmentioning
confidence: 98%
“…Necrostatin protects by inhibiting RIP1 kinase activation with possible downstream antiinflammatory effects (You et al, 2008) and perhaps other mechanisms. Although necrostatin has no intrinsic antioxidant activity, it blocks tumor necrosis factor (TNF)-induced activation of NADPH (nicotinamide adenine dinucleotide phosphate) oxidase (Kim et al, 2007) and nitric oxide-mediated necrosis (Davis et al, 2010) by the inhibition of both Nox1 and mitochondrialderived oxygen-free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…No differences in visible platform performance were noted among CHI groups (P ¼ 0.71 for group) and no differences in hidden, visible platform, or probe trials were noted between CHI-VEH and CHI-Akt viii groups. mTOR and Akt in concussive brain injury X Zhu et al after CCI; 17,18 however, Nec-1 has not been reported in a non-cell death TBI model. The current study suggests a possible link between the beneficial effects of Nec-1 on cognitive function and augmentation of Akt/mTOR signaling after CHI, a finding that lends support to the possibility that Akt/mTOR signaling is a protective response to CHI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that Nmnat1 mediates its axonal protective effect in the presence of activated caspase-6 after tropic factor deprivation in dorsal root ganglion neurons (18). Interestingly, necrostatin, a small-molecule inhibitor of programmed necrosis (necroptosis), also fails to inhibit the activation of the caspase-3 pathways in animal models of neonatal brain injury (47) even though it provides significant protection in neonatal H-I and other mice models of acute injury (47)(48)(49). Whether the pathways activated by Nmnat1 and necrostatin overlap is unclear and will be an important area for future study.…”
Section: Discussionmentioning
confidence: 99%